2005
DOI: 10.1007/s10447-005-2255-x
|View full text |Cite
|
Sign up to set email alerts
|

Cybercounseling: A New Modality for Counselor Training and Practice

Abstract: The practice of professional career counseling has evolved to include various computer technologies and services including the Internet. Due to the Internet becoming a pervasive part of society, increasing numbers of mental health practitioners around the world are incorporating the electronic medium into their service delivery. As increasing numbers of counselors use the Internet, professional organizations are developing ethical guidelines for practitioners to follow. This paper discusses ethical considerati… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
19
0
2

Year Published

2009
2009
2020
2020

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 22 publications
(21 citation statements)
references
References 16 publications
0
19
0
2
Order By: Relevance
“…Tait (1999) acknowledged that fears of human relations becoming mechanized because of ICT are real, but suggested that human relations would not necessarily be diminished-only changed. The adoption of an ICT-based modality for counseling would demand that certain ethical and technical standards be set to govern the conduct of the counselor, ensure the safety of the client, and promote the counseling profession (Mallen et al 2005;McCrickard and Butler 2005).…”
Section: Discussionmentioning
confidence: 99%
“…Tait (1999) acknowledged that fears of human relations becoming mechanized because of ICT are real, but suggested that human relations would not necessarily be diminished-only changed. The adoption of an ICT-based modality for counseling would demand that certain ethical and technical standards be set to govern the conduct of the counselor, ensure the safety of the client, and promote the counseling profession (Mallen et al 2005;McCrickard and Butler 2005).…”
Section: Discussionmentioning
confidence: 99%
“…For each of these, there is a modern computer-mediated equivalent. Advanced letter composition regularly happens through mail and electronic bulletin boards; synchronous connections (i.e., those taking part at the same time as the pastoral/spiritual counselor or psychologist and counselee/client) incorporate voice-over-Internet protocol (VOIP), video-conferencing apps, instant messaging (IM), and chat, which contrasts with short-message service (SMS), its phone-based counterpart ( Centore & Milacci, 2008 ; Kessler et al., 2009 ; McCrickard & Butler, 2005 ; Mallen & Vogel, 2005 ).…”
Section: The History and Concept Of Online/cyber Counselingmentioning
confidence: 99%
“…Pastoral/spiritual counselors or psychologists who have adequate technical ability can progressively communicate with their counselee/client through the online medium and/or undertake the whole progress online (Mallen & Vogel, 2005). The benefits of online/cyber counseling incorporate more noteworthy availability, reaching populaces that would not immediately look for face-to-face counseling, reasonableness, and ease of record keeping (Leibert et al, 2006;McCrickard & Butler, 2005;Rochlen et al, 2004). Moreover, Suler (2002) and Partala (2011) expressed that counselees/clients taking part in online/cyber counseling are less likely to feel powerless for revealing their individual data and also feel less ashamed about their issues, due to the anonymity related to online/cyber counseling.…”
Section: Introductionmentioning
confidence: 99%
“…Pero además, la incorporación de las TIC no está exenta de aspectos éticos (Mallen, Vogel y Rochlen, 2005;McCrickard y Butler, 2005;Valverde y Fernández 2013)y, por tanto, estos deben estar presentes en los análisis que se realicen sobre esta temática y hay que tomar conciencia de sus repercusiones cuando se intente ofrecer la tecnología como herramienta necesaria a los profesionales de la orientación. Evitar suspicacias como las relativas al cuestionamiento de su labor cuando se recomienda introducir las TIC o incluso disipar el miedo de algunos a que la tecnología pueda sustituirles en su labores de orientación, son aspectos que no deben obviarse (Sobrado, 2006).…”
Section: Discusión Y Prospectivaunclassified